2004
DOI: 10.3928/1081-597x-20040903-19
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Microkeratome Complications in 47,094 Laser in situ Keratomileusis Surgeries

Abstract: PURPOSE: We evaluated the incidence and intraoperative microkeratome-related complications in laser in situ keratomileusis (LASIK). METHODS: We present non-randomized, retrospective, comparative, interventional case series. We reviewed the records of patients who underwent LASIK from August 2000 to March 2004 at Excimer Laser Santa Cruz, São Paulo, Brazil (47,094 eyes). We identified 369 eyes (0.0078%) with an intraoperative complication. Data were collected regarding microkeratome, average keratomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…[4][5][6] Flap complication rates have been reported from 0.3% to 14%, depending on the microkeratome and surgeons involved. [7][8][9][10][11] Few studies were found regarding the relationship between fl ap complication rates and preoperative keratometric power. 2,5 Results of patients having undergone LASIK at our centers with a manual, mechanical microkeratome (Moria LSK One; Moria, Antony, France) were analyzed to assess the relationship between preoperative keratometric power and intraoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Flap complication rates have been reported from 0.3% to 14%, depending on the microkeratome and surgeons involved. [7][8][9][10][11] Few studies were found regarding the relationship between fl ap complication rates and preoperative keratometric power. 2,5 Results of patients having undergone LASIK at our centers with a manual, mechanical microkeratome (Moria LSK One; Moria, Antony, France) were analyzed to assess the relationship between preoperative keratometric power and intraoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 17 243 LASIK procedures, there were 86 cases of suction loss, which gives exactly the same incidence of 0.50% that was found for SMILE. Table 6 shows the published suction loss incidence for the IntraLase femtosecond laser (Johnson & Johnson Vision, Jacksonville, FL, USA) (Binder 2006;Chang 2008;Sutton & Hodge 2008;Haft et al 2009;Davison & Johnson 2010;Moshirfar et al 2010;Kohnen et al 2016) and the Hansatome microkeratome (Bausch & Lomb, Rochester, NY, USA) (Jacobs & Taravella 2002;Nakano et al 2004;Moshirfar et al 2010;Al-Mezaine et al 2011) for studies with a population of more than 750 eyes. The overall suction loss rate was found to be 0.18-0.19% for both, which is just over half the rate for SMILE.…”
Section: Discussionmentioning
confidence: 99%
“…Операции ЛАЗИК присущи недостатки, которые, главным образом, координированы с работой микрокератома: тонкий неравномерный клапан, прободение (button hole), микрострии, децентрация, смещение клапана, полный (free flap) и неполный срез клапана, индуцированная кератэктазия, обнаружение микрочастиц металла в роговице. Все это, несомненно, сказывается на качестве зрительных функций в послеоперационном периоде [14][15][16][17].…”
Section: эволюция современных методов лазерной хирургии роговицыunclassified